Active Dynamic Records Management System in the Regional Research and Development Agency (Balitbangda) of South Sulawesi Province - Lebang, Romi R (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the management system of active dynamic records at the Regional Research and Development Agency of South Sulawesi Province (Balitbangda Sulsel) through four main aspects as outlined by Saransi (2014), namely creation, classification, storage and filing, as well as preservation and maintenance. The research employed a qualitative descriptive approach, allowing the researcher to gain an in-depth understanding of archival management practices in the field. Primary data were collected through in-depth interviews with the head of the agency, staff, and archivists directly involved in records management, while secondary data were obtained from documents, historical reports, and official records. The findings indicate that record creation at Balitbangda Sulsel has been carried out in accordance with organizational functions; however, record classification remains inconsistent, leading to difficulties in document retrieval. The aspects of storage and filing also face challenges, including limited physical facilities, non-standard filing cabinets, and storage rooms shared with the library and reading area. Preservation and maintenance of records are not yet optimal due to limited facilities and insufficient attention from leadership to storage conditions, posing risks to the physical quality and security of records. This study emphasizes that effective management of active dynamic records requires integration of formal archival standards, adequate facilities, and the utilization of digital technology to support the accuracy, effectiveness, and sustainability of organizational information. These findings can serve as the basis for recommendations to strengthen archivists’ capacity, provide appropriate archival facilities, and implement record digitization as a strategic step in modern archival management.